2022
DOI: 10.1021/acsami.2c05149
|View full text |Cite
|
Sign up to set email alerts
|

Improved Durability of High-Performance Intermediate-Temperature Solid Oxide Fuel Cells with a Ba-Doped La0.6Sr0.4Co0.2Fe0.8O3−δ Cathode

Abstract: As a device for direct conversion of chemical energy into electrical energy, the solid oxide fuel cell (SOFC) contributes positively to the sustainable development strategy. However, the commercialization of fuel cells is still impeded by severe cathode degradation caused by its limited stability at operating temperatures and being prone to Cr-poisoning from Cr-containing alloy interconnectors commonly used in these cells. This paper reports the development of a high-durability Ba-doped LSCF(La 0.6 Sr 0.4 Co 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The significant Cr tolerance of Ba-containing cathodes or promoters has also been observed by many research groups. [17][18][19][20][21][22][23][24][25][26]31,34,69] The Cr tolerance mechanism of the CC-LSCF cathode is schematically illustrated in Figure 8.…”
Section: Mechanism Of Enhanced Durability By Catalyst Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant Cr tolerance of Ba-containing cathodes or promoters has also been observed by many research groups. [17][18][19][20][21][22][23][24][25][26]31,34,69] The Cr tolerance mechanism of the CC-LSCF cathode is schematically illustrated in Figure 8.…”
Section: Mechanism Of Enhanced Durability By Catalyst Coatingmentioning
confidence: 99%
“…[ 8–10 ] Volatile Cr species can also be captured by inserting a layer of catcher material on the cathode, [ 11,12 ] although maintaining the adsorption capability and structural stability of the catcher is challenging in the harsh environment. Researchers have also developed Cr‐resistant cathode materials, such as La(Ni, Fe)O 3–δ [ 13,14 ] and Re 2 NiO 4–δ (Re = Nd, La, Pr), [ 15,16 ] as well as Ba‐containing [ 17–24 ] and high‐entropy perovskite electrodes. [ 25–27 ] However, relying on a single phase to simultaneously meet the stringent requirements of an ideal cathode, such as high electrocatalytic activity and excellent Cr durability, is almost impossible, whereas the design and development of a multiphase cathode provides new opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…The attention was quickly shifted to perovskite oxides (see Note below), such as La 1-x Sr x MnO 3 , when it was discovered to have excellent oxygen catalytic activity at 800-1,000 °C [12] . However, as a pure electronic conductor, the ORR could only occur at the interface of the cathode and electrolyte [13] . This results in very limited catalytic efficiency of the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…While several air electrode materials have been presented, most of them only exhibit insufficiently high electrochemical performance in R-PCECs, even though considerable attempts have been made in the past few decades. Considerable studies have concluded that Co-containing air electrode materials exhibit high catalytic activity in both ORR ,, and OER. ,, La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3‑δ (LSCF6428), as one of the traditional mixed ionic and electronic air electrode materials, has been widely used in oxygen-ion conducting solid oxide fuel cells (O-SOFCs) and protonic ceramic fuel cells (PCFCs) , due to its excellent catalytic activity. However, the performance of cells with LSCF6428-based air electrodes shows a fast degradation since Sr segregation on the air electrode surface is prone to forming another destructive secondary phase (such as SrCO 3 , SrO or Sr­(OH) 2 ), limiting the catalytic activity of electrode materials. , Designing a Sr-free Co-based air electrode with high activity has recently attracted great attention. ,, Due to its excellent electronic conductivity and oxygen ionic conductivity, rapid oxygen surface exchange, and oxygen ion bulk diffusion kinetics, a double-perovskite material PrBaCo 2 O 5+δ (PBC) has demonstrated desirable electrochemical performance as the air electrode for SOFCs. , For instance, Ca-doped PBC (PrBa 0.8 Ca 0.2 Co 2 O 5+δ ) double-perovskite oxide exhibited an outstanding ORR electrocatalytic activity as a highly promising electrode material for SOFCs .…”
mentioning
confidence: 99%